CARE OF THE ELDERLY WITH ALZHEIMER'S IN LONG-STAY INSTITUTIONS. - Astrês Fernandes¹, Márcia; Oliveira Galvão Sousa, José Willyans; Silva de Sousa, Wendes; de Deus Gomes, Lucas Freitas; Pinheiro Landim Almeida, Camila Aparecida; Carvalho Sena Damasceno, Carolline Klicia; Batista de Carvalho, Ana Raquel; de Sousa Ibiapina, Aline Raquel (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2018)
Objective: to analyze the care provided by caregivers for the elderly with Alzheimer's in Long-Stay Institution. Method: a qualitative study, descriptive-exploratory, conducted through interviews, with 14 professionals from an institution of long-stay, processed with the IraMuTeQ software. Results: there were obtained five semantic classes, namely: Class 2-The routine of care given by professionals of the institution; Class 1-The importance of the elderly care professionals with signs of the effects of Alzheimer's: difficulties of concentration and memory; Class 4-Memory lapses of the elderly with Alzheimer's disease; Class 5-The role of the professional in the full care to the elderly with Alzheimer's; Class 3-Absence of the family in the care for the elderly with Alzheimer's. Conclusion: the care is good, but negative points have been observed as idleness of the elderly, family, and absence of scientific-theoretical knowledge deficit on the part of some professionals.